Microencapsulation of Berberine to Develop a Natural Antibacterial Delivery System for Drinking Water - Sanliturk, Gizem; Mustafa, Faisal Suleiman; Guran, Muemtaz; Dogan, Sifa; Gazi, Mustafa (Pleiades Publishing Ltd, 2024)
In this study, we aimed to fabricate a novel, completely natural antibacterial disinfectant material for environmental applications, such as treating drinking water. We created two different berberine-alginate (BerAlg) beads using the ionotropic gelation method, employing calcium and aluminium ions as cross-linkers. The materials were characterized using Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), swelling, and release kinetic studies. Antibacterial activity was assessed through time-kill analysis. Among the four release kinetics models tested, the BerAlg bead formulation showed the best fit with the Korsmeyer-Peppas model, having the highest R2 value (0.9757). The longest release of berberine (Ber) was observed over a 4-h period. The time-kill assay results revealed that BerAlg beads were effective in killing for up to 7 h. In conclusion, these results demonstrate the promising potential of BerAlg beads as an antibacterial delivery system for disinfecting various liquid environments, such as drinking water.
Keywords: sodium alginate; S. aureus; berberine; drinking water; antibacterial